2010
DOI: 10.1007/s12029-009-9125-4
|View full text |Cite
|
Sign up to set email alerts
|

The Baseline Ratio of Neutrophils to Lymphocytes is Associated with Patient Prognosis in Rectal Carcinoma

Abstract: These results suggest that the N/L ratio is an independent prognostic factor in rectal cancer, and the N/L ratio may serve as a clinically accessible and useful biomarker for patient survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 25 publications
0
43
0
Order By: Relevance
“…From then on, a large number of clinical studies have been performed to understand the neutrophil-cancer relationship. Clinical data have often related elevated circulating neutrophil counts or elevated neutrophil-to-lymphocyte ratios (NLRs) as a predictive parameter for poor outcome and formation of distant metastasis in patients with epithelial malignancies [367], including lung [368,170], gastric [159,163,369], renal cell carcinoma [370], ovarian [141], hepatic [143,148,371], pancreatic [138], colon cancer [145,372], and colorectal carcinoma [152] (Table 3). However, Caruso et al [200] observed that when analyzing the amount of tumor-infiltrated neutrophils in advanced gastric carcinoma, in female but not male, patients with higher TANs had a favorable prognosis.…”
Section: Prognostic Values Of Neutrophils and Other Myeloid Subtypes mentioning
confidence: 99%
“…From then on, a large number of clinical studies have been performed to understand the neutrophil-cancer relationship. Clinical data have often related elevated circulating neutrophil counts or elevated neutrophil-to-lymphocyte ratios (NLRs) as a predictive parameter for poor outcome and formation of distant metastasis in patients with epithelial malignancies [367], including lung [368,170], gastric [159,163,369], renal cell carcinoma [370], ovarian [141], hepatic [143,148,371], pancreatic [138], colon cancer [145,372], and colorectal carcinoma [152] (Table 3). However, Caruso et al [200] observed that when analyzing the amount of tumor-infiltrated neutrophils in advanced gastric carcinoma, in female but not male, patients with higher TANs had a favorable prognosis.…”
Section: Prognostic Values Of Neutrophils and Other Myeloid Subtypes mentioning
confidence: 99%
“…Cancer is an inflammatory condition and the available treatments are associated with an acute inflammatory state, be it through tissue trauma, infectious complications, or tumor-mediated inflammation (3). A portion of this literature has focused on the clinical observation that elevated neutrophil counts or elevated neutrophil-to-lymphocyte ratios are predictive of poor outcomes and distant metastasis in patients with a wide array of epithelial malignancies including lung (4), gastric (5), ovarian (6), hepatic (6), pancreatic (7), and colon carcinomas (8). Neutrophils become activated in response to inflammatory stimuli and have widespread effects on organs that commonly harbor metastases such as the lung and the liver (9).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous patients suffering from these advanced cancers eventually succumb to the disease (2)(3)(4). Various molecular biomarkers have been used to identify the baseline parameters predicting patient prognosis in various studies, but technical factors and excessive costs preclude their clinical use.…”
Section: Introductionmentioning
confidence: 99%